Epigenetic Regulators Modulate Muscle Damage in Duchenne Muscular Dystrophy Model - Bajanca, Fernanda (PLoS Curr, 2017)
Histone acetyl transferases (HATs) and histone deacetylases (HDAC) control transcription during myogenesis. HDACs promote chromatin condensation, inhibiting gene transcription in muscle progenitor cells until myoblast differentiation is triggered and HDACs are released. HATs, namely CBP/p300, activate myogenic regulatory and elongation factors promoting myogenesis. HDAC inhibitors are known to improve regeneration in dystrophic muscles through follistatin upregulation. However, the potential of directly modulating HATs remains unexplored. We tested this possibility in a well-known zebrafish model of Duchenne muscular dystrophy. Interestingly, CBP/p300 transcripts were found downregulated in the absence of Dystrophin. While investigating CBP rescuing potential we observed that dystrophin-null embryos overexpressing CBP actually never show significant muscle damage, even before a first regeneration cycle could occur. We found that the pan-HDAC inhibitor trichostatin A (TSA) also prevents early muscle damage, however the single HAT CBP is as efficient even in low doses. The HAT domain of CBP is required for its full rescuing ability. Importantly, both CBP and TSA prevent early muscle damage without restoring endogenous CBP/p300 neither increasing follistatin transcripts. This suggests a new mechanism of action of epigenetic regulators protecting dystrophin-null muscle fibres from detaching, independent from the known improvement of regeneration upon damage of HDACs inhibitors. This study builds supporting evidence that epigenetic modulators may play a role in determining the severity of muscle dystrophy, controlling the ability to resist muscle damage. Determining the mode of action leading to muscle protection can potentially lead to new treatment options for muscular dystrophies in the future.